Alysicarpus bhuibavadensis (Fabaceae) a new species from Western Ghats of India - Dalavi, Jagdish Vishnu; Bramhadande, Sneha; Pokle, Deelip; Yadav, Shrirang (Phytotaxa, 2019)
Alysicarpus bhuibavadensis is described here as a new species from Sindhudurg district of Maharashtra state, India. Alysicarpus bhuibavadensis is close to A. tetragonolobus and A. gracilis in its morphology but distinct by means of pubescent leaves, axillary lax racemes, included pods with thickened beak.